Tinjauan Hukum Islam Terhadap Adat Pernikahan Habaib (Studi Kasus Praktik Pernikahan Keluarga Habaib Di Sangatta) - Ahmad Abrar; Musthato’ Musthato’; Anggra Prima (CV. ITTC INDONESIA, 2025)
This study aims to analyze the marriage customs of Habaib in Sangatta from the perspective of Islamic law, focusing on the harmonization between customs and the principles of sharia. This research uses a descriptive qualitative method with a phenomenological approach to explore the subjective experiences of the perpetrators of Habaib marriage customs. The results showed that although the Habaib marriage custom in Sangatta still maintains the principle of maintaining lineage according to Islamic law, there is flexibility in adjusting some aspects of tradition to local culture. The marriage process is still carried out according to the pillars of Islam, and also the Habaib marriage custom in Sangatta reflects efforts to preserve traditional values that are considered sacred. however, harmonization between customary values and Islamic legal principles is needed so that the implementation of marriage remains inclusive and non-discriminatory.